2015
DOI: 10.1039/c5nr05790f
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic transformation towards formation of nanotubes by self-assembly of an achiral molecule

Abstract: In this paper, nanotubes with a uniform diameter were prepared by self-assembly of an achiral azobenzene-containing fatty acid. The polymorphic transformation of the assemblies during the cooling process was systematically studied. By controlling the incubation temperature, different morphologies, such as membranes, stripes, helical ribbons and tubes, were all obtained in our experiment. These elements were all predicted by Selinger et al. in the theoretical model of the formation of nanotubes. To the best of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…Prior to self-assembly, BBA-12C displays ν as (CH 3 ), ν as (CH 2 ), and ν s (CH 2 ) at 2954, 2918, and 2850 cm –1 , respectively (Figure f). After self-assembly, the asymmetric and symmetric stretching vibrations of CH 2 appear at 2916 and 2848 cm –1 , respectively; the lowered frequencies suggest the all-trans conformation of hydrocarbon chains. , Taken together, these results suggest that BBA-12C molecules are closely and orderly packed within the 2D nanosheets in a multilayered manner.…”
Section: Results and Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Prior to self-assembly, BBA-12C displays ν as (CH 3 ), ν as (CH 2 ), and ν s (CH 2 ) at 2954, 2918, and 2850 cm –1 , respectively (Figure f). After self-assembly, the asymmetric and symmetric stretching vibrations of CH 2 appear at 2916 and 2848 cm –1 , respectively; the lowered frequencies suggest the all-trans conformation of hydrocarbon chains. , Taken together, these results suggest that BBA-12C molecules are closely and orderly packed within the 2D nanosheets in a multilayered manner.…”
Section: Results and Discussionmentioning
confidence: 73%
“…We note that in order to introduce more functionalities into the bolaamphiphile, the biphenyl group of BBA was substituted with the azobenzene group, yielding photoresponsive anionic bolaamphiphile ( E )-4,4′-((diazene-1,2-diylbis­(4,1-phenylene))­bis­(azanediyl))­bis­(4-oxobutanoic acid) (denoted OBA; see the Experimental Section). It is well-known that the trans-isomer of azobenzene has a planar rigid configuration, making it an ideal building block to construct 2D structures. ,, The implementation of the OBA – /TMG + complex as the building block synthesized by the reaction of BOA and TMG produces several-micron-sized, single-layered 2D nanosheets consisting of OBA – /TMG + complexes (Figure d). This result suggests that changing the biphenyl core to azobenzene has negligible influence on the self-assembly morphology due to the comparable π–π stacking interaction strength of azobenzene moieties to that of the biphenyl moieties.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the structures observed in ref. 44, even after 2 months of equilibration, were rather defective, short in lengths, suggesting that they have not yet reached equilibrium. Although the exact mechanism responsible for the formation of chiral nanostructures in achiral systems is still a matter of debate, [45][46][47][48] these previous studies have clearly demonstrated that chiral nanostructures can be realized via self-assembly of achiral molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In these systems, the induction of chirality in the resulting nanostructures was attributed to symmetry breaking phenomena with respect to molecular tilt or conformation. In a recent study, Wang et al 44 have demonstrated the formation of a collection of alternative structures (like nanotubes, helical ribbons, stripes and membranes) in solutions of achiral azobenzene-based molecules, which are capable of performing a reversible cis-trans transformation. As cisconformations result in chiral centers within these molecules, such symmetry breaking may induce chiral structures.…”
Section: Introductionmentioning
confidence: 99%